The Concept of Law and Market Mechanism According to Ibn Khaldun and Imam Al-Ghazali - Muhammad Abdul Aziz; Muhammad Rayhan; Muhammad Isa (Al-Muamalat: Journal of Islamic Economics Law, 2025)
ENGLISH The market mechanism in Islamic Economics emphasizes the need for balance (iqtishad) between the market, the state, and the individual, rejecting the dominance of one over the others , which differs from conventional markets that often experience distortions. This research is a conceptual study that analyzes the market mechanism concepts of two Islamic economic scholars: Ibn Khaldun (through his Muqaddimah) and Imam Al-Ghazali (through Ihya’ Ulumuddin). The research findings indicate that according to Ibn Khaldun, a nation's wealth is determined by its production level , the value of a product is equal to the amount of labor it possesses , and prices are determined by the law of supply and demand. He views gold and silver as the most suitable measures of value and monetary standards. Furthermore, the product price is distributed into three factors: income (producer's wage), profit (merchant's compensation), and tax (compensation for state officials/rulers). Meanwhile, Imam Al-Ghazali links all economic activities to morals and ethics , explains market movements by describing the shape of the supply curve (rising from bottom left) and the demand curve (descending from top right) , and asserts that the motive for trading must be to seek profit in this world and the hereafter, not just worldly profit. He considers the production of basic necessities a social obligation (fard al-kifayah). Overall, both figures conclude that the market must operate justly according to norms and principles derived from the Qur'an and Hadith. INDONESIA Mekanisme pasar dalam Ekonomi Islam menekankan perlunya keseimbangan (iqtishad) antara pasar, negara, dan individu, serta menolak dominasi satu pihak atas pihak lain, yang berbeda dengan pasar konvensional yang sering mengalami distorsi. Penelitian ini merupakan studi konseptual yang menganalisis konsep mekanisme pasar dari dua cendekiawan ekonomi Islam: Ibnu Khaldun (melalui Muqaddimah) dan Imam Al-Ghazali (melalui Ihya’ Ulumuddin). Temuan penelitian menunjukkan bahwa menurut Ibnu Khaldun, kekayaan suatu bangsa ditentukan oleh tingkat produksinya, nilai suatu produk setara dengan jumlah tenaga kerja yang dimilikinya, dan harga ditentukan oleh hukum permintaan dan penawaran. Ia memandang emas dan perak sebagai ukuran nilai dan standar moneter yang paling sesuai. Selanjutnya, harga produk didistribusikan ke dalam tiga faktor: pendapatan (upah produsen), keuntungan (kompensasi pedagang), dan pajak (kompensasi untuk pejabat negara/penguasa). Sementara itu, Imam Al-Ghazali mengaitkan semua aktivitas ekonomi dengan moral dan etika, menjelaskan pergerakan pasar dengan mendeskripsikan bentuk kurva penawaran (naik dari kiri bawah) dan kurva permintaan (turun dari kanan atas), serta menegaskan bahwa motif berdagang haruslah untuk mencari keuntungan di dunia dan akhirat, bukan hanya keuntungan duniawi. Ia menganggap produksi kebutuhan pokok sebagai kewajiban sosial (fardhu kifayah). Secara keseluruhan, kedua tokoh tersebut menyimpulkan bahwa pasar harus beroperasi secara adil sesuai dengan norma dan prinsip yang bersumber dari Al-Qur'an dan Hadis.